President Mandela’s Admiral: The South African Navy’s Story of the 1990s: Challenging Politics, Radical Transformation, Ambitious Voyages and the Quest for New Ships and Submarines - Steyn, Leon (Scientia Militaria - South African Journal of Military Studies, 2023)
FYI